Profit Shifting and Investment Effects: The Implications of Zero-Taxable Profits - Marko Köthenbürger; Mohammed Mardan; Michael Stimmelmayr (Center for Economic Studies and ifo Institute (CESifo), 2018)
Recent empirical research documents a tendency of affiliates of multinational enterprises to bunch around zero reported profit. Setting up a model that allows for profitable and loss-making affiliates of multinationals, we show that profit shifting to a low-tax country as well as a loss-related, inverted-type of transfer pricing from the low-tax to the high-tax country induces bunching. Such bunching promotes investment incentives in the low-tax as well as the high-tax country. In equilibrium, affiliates might over-invest and the bunching-related investment effects generate a tendency for too high profit taxes in equilibrium. The finding contrasts existing literature where transfer pricing incentives are insulated from investment incentives and transfer pricing induces inefficiently low taxes.
Keywords: H25; D21; H87; 330; tax competition; profit shifting; corporate losses; bunching; investment